Prevalence, Clinical Phenotype, and Outcomes Associated With Normal B-Type Natriuretic Peptide Levels in Heart Failure With Preserved Ejection Fraction - Anjan, Venkatesh Y.; Loftus, Timothy M.; Burke, Michael A.; Akhter, Nausheen; Fonarow, Gregg C.; Gheorghiade, Mihai; Shah, Sanjiv J. (The American journal of cardiology, 2012)
B-type natriuretic peptide (BNP) is used widely to exclude heart failure (HF) in patients with dyspnea. However, most studies of BNP have focused on diagnosing HF with reduced ejection fraction (EF). The aim of this study was to test the hypothesis that a normal BNP level (≤100 pg/ml) is relatively common in HF with preserved EF (HFpEF), a heterogenous disorder commonly associated with obesity. A total of 159 consecutive patients enrolled in the Northwestern University HFpEF Program were prospectively studied. All subjects had symptomatic HF with EF >50% and elevated pulmonary capillary wedge pressure. BNP was tested at baseline in all subjects. Clinical characteristics, echocardiographic parameters, invasive hemodynamics, and outcomes were compared among patients with HFpEF with normal (≤100 pg/ml) versus elevated (>100 pg/ml) BNP. Of the 159 patients with HFpEF, 46 (29%) had BNP ≤100 pg/ml. Subjects with normal BNP were younger, were more often women, had higher rates of obesity and higher body mass index, and less commonly had chronic kidney disease and atrial fibrillation. EFs and pulmonary capillary wedge pressures were similar in the normal and elevated BNP groups (62 ± 7% vs 61 ± 7%, p = 0.67, and 25 ± 8 vs 27 ± 9 mm Hg, p = 0.42, respectively). Elevated BNP was associated with enlarged left atrial volume, worse diastolic function, abnormal right ventricular structure and function, and worse outcomes (e.g., adjusted hazard ratio for HF hospitalization 4.0, 95% confidence interval 1.6 to 9.7, p = 0.003). In conclusion, normal BNP levels were present in 29% of symptomatic outpatients with HFpEF who had elevated pulmonary capillary wedge pressures, and although BNP is useful as a prognostic marker in HFpEF, normal BNP does not exclude the outpatient diagnosis of HFpEF.